Efficient induction of pancreatic alpha cells from human induced pluripotent stem cells by controlling the timing for BMP antagonism and activation of retinoic acid signaling. - Shigeharu G Yabe; Satsuki Fukuda; Junko Nishida; Fujie Takeda; Kiyoko Nashiro; Hitoshi Okochi (PLoS ONE, 2021)
Diabetes mellitus is caused by breakdown of blood glucose homeostasis, which is maintained by an exquisite balance between insulin and glucagon produced respectively by pancreatic beta cells and alpha cells. However, little is known about the mechanism of inducing glucagon secretion from human alpha cells. Many methods for generating pancreatic beta cells from human pluripotent stem cells (hPSCs) have been reported, but only two papers have reported generation of pancreatic alpha cells from hPSCs. Because NKX6.1 has been suggested as a very important gene for determining cell fate between pancreatic beta and alpha cells, we searched for the factors affecting expression of NKX6.1 in our beta cell differentiation protocols. We found that BMP antagonism and activation of retinoic acid signaling at stage 2 (from definitive endoderm to primitive gut tube) effectively suppressed NKX6.1 expression at later stages. Using two different hPSCs lines, treatment with BMP signaling inhibitor (LDN193189) and retinoic acid agonist (EC23) at Stage 2 reduced NKX6.1 expression and allowed differentiation of almost all cells into pancreatic alpha cells in vivo after transplantation under a kidney capsule. Our study demonstrated that the cell fate of pancreatic cells can be controlled by adjusting the expression level of NKX6.1 with proper timing of BMP antagonism and activation of retinoic acid signaling during the pancreatic differentiation process. Our method is useful for efficient induction of pancreatic alpha cells from hPSCs.